The impact of visual merchandising elements on consumer attention: a case study of retail stores in Malaysia's domestic and international markets - Megat Zambri, Megat Amirul Ashraf; Saleh, Maarof; Megat Zambri, Wan Anis Aqilah (Faculty of Art and Design, 2025)
Visual merchandising plays the largest role of influencing the consumer behavior and buying behavior in retail stores. This study looks into the influence of visual merchandising materials like color palette, design of the layout, lighting, signs, and arrangement of goods to the attention given by the consumer to the store outlets. The methodology of the study is a qualitative case study, and the researchers studied domestic and international retail stores present in the Malaysian market which is a diverse market. The research determined the visual characteristics ideal in attracting the attention of consumers through in-store observations, questionnaires (i.e. internal consumer’s interviews) and focus groups (i.e. internal consumer’s group discussions) on sensory stimulation to consumers. It is determined that the shops with the thoughtful color palette, correct locations of the products and the careful use of lighting increase the period of time the customers spend in the store. In addition, the layout of the store and effective signage are also important to direct the shoppers throughout the store thus they have a wonderful time spent shopping. The study is of great help to Malaysian retailers, given some of the strategies related to use of visual merchandising to attract and maintain customers, enhance the store design and remain competitive in the rapidly changing retail environment.